Pengaruh Penggunaan Konten Dance TikTok Terhadap Motorik Kasar Anak Usia 5-6 Tahun di TK Nusa - Dawe, Maryani; Herlina; Kurnia R, Rika (Jambura Early Childhood Education Journal, 2024)
This research aims to determine whether or not there is an effect of using Tik Tok dance content on the gross motor development of children aged 5-6 years at Nusa Makassar Kindergarten before and after being given treatment. The research approach used is a quantitative approach with a Quasi Experimental Design type of research. Sampling in this research used purposive sampling. The sample in this study was 20 children, 10 children as the control group and 10 children as the experimental group. The data analysis techniques used are descriptive statistical analysis and non-parametric statistical analysis. Based on the research results, it can be concluded that the gross motor skills of children who were given treatment to imitate dance movements in the experimental group were better than those in the control group. The results of data analysis showed an average increase in the experimental group of 8.1 while in the control group it was 5.5 and the test results showed a sig. (2-tailet) 0.004 < 0.05, then H0 is rejected and H1 is accepted, this proves that the use of tik tok dance content has a significant influence on the gross motor skills of children aged 5-6 years at Nusa Makassar Kindergarten.